(untitled) - Needham, Christy; Ku, Kim (New York, 2020)
"This Big Fat Notebook covers everything you need to know during a year of high school geometry class, breaking down one big bad subject into accessible units. Learn to study better and get better grades using mnemonic devices, definitions, diagrams, educational doodles, and quizzes to recap it all."--
Parallel lines --
Keywords: Study and teaching; Geometry; Juvenile literature; Study and teaching; Geometry; Geometry; Study guides; Study guides